Building a Strong Foundation in English with Phonics Method among the First Graders of Elementary School in Magelang - Putri, Aprilian; Jayanti, Widya; Fortinasari, Paulina; Putri, Nabila; Meili Amandha; Firdaus, Muhammad (Satya Widya, 2024)
This study aims to assess the efficacy of the phonics method in improving the English language proficiency of Indonesian first-grade elementary school students. The core group of 32 participants consisted of fifteen female and seventeen male students in the observation and interview techniques used to collect data. The results of this study showed that the phonics method can help increase the vocabulary of early childhood students, as the students can pronounce the letters correctly and remember the sounds of the letters and words. The findings show that the phonics method strengthens their early understanding of English by assisting first-graders in building a solid foundation. The study's findings showed that there are differences in the learning outcomes of beginning reading in students who follow the use of audio-visual media and in students who do not use audio-visual. Phonic method helped students build a solid foundation in reading, which in turn strengthened their foundation for English language proficiency. This study emphasizes the importance of phonics as a powerful teaching tool for developing reading skills in the early stages of formal education.